Burundi Country Environmental Analysis : Understanding the Environment within the Dynamics of a Complex World—Linkages to Fragility, Conflict, and Climate Change - World Bank Group (World Bank, Washington, DC, 2017)
Over the past decades, Burundi's economic growth has relied on steady depletion of its natural capital, and as a result, the country's natural environment has been substantially degraded. The main driver of environmental degradation has been rapid population growth. In particular, to feed the growing population, substantial areas of forest have been cleared for agriculture, and poor agricultural practices have harmed soil fertility and integrity. Water resources have also been degraded, affecting several sectors and public health. In addition, biofuel burning continues to expose the population to severe indoor air pollution. In some cases, climate change is amplifying these consequences, particularly the frequency and severity of natural disasters. Without proper institutional arrangements in place, the environment has not been safeguarded from the expansive forces. Further, environmental degradation and resulting resource scarcity have led to conflicts, and, in turn, conflict and fragility have aggravated environmental degradation.